"For great in your midst is the Holy One of Israel" (Is 12:6b): Trauma and resilience in the Isaianic Psalm - Groenewald, Alphonso (HTS teologiese studies, 2017)
This article focuses on Isaiah 12 – an important text that concludes the first main section of the Book of Isaiah (BI). The analysis focuses on the structure and redaction of this text. The text is interpreted as a meaning-making text against the background of trauma as described in this first main section of the BI.